Conversion to Secondary Progressive Multiple Sclerosis: Patient Awareness and Needs. Results From an Online Survey in Italy and Germany - Solari, Alessandra; Giovannetti, Ambra Mara; Giordano, Andrea; Tortorella, Carla; Torri Clerici, Valentina; Brichetto, Giampaolo; Granella, Franco; Lugaresi, Alessandra; Patti, Francesco; Salvetti, Marco; Pesci, Ilaria; Pucci, Eugenio; et al. (Frontiers in Neurology, 2019)
Background. Few studies have investigated the experiences of patients around the conversion to secondary progressive multiple sclerosis (SPMS). ManTra is a mixed-method, co-production research project conducted in Italy and Germany to develop an intervention for newly-diagnosed SPMS patients. In previous project actions, we identified the needs and experiences of patients converting to SPMS via literature review and qualitative research which involved key stakeholders. Aims. The online patient survey aimed to assess, on a larger and independent sample of recently-diagnosed SPMS patients: (a) the characteristics associated to patient awareness of SPMS conversion; (b) the experience of conversion; (c) importance and prioritization of the needs previously identified. Methods. Participants were consenting adults with SPMS since ≤5 years. The survey consisted of three sections: on general and clinical characteristics; on experience of SPMS diagnosis disclosure (aware participants only); and on importance and prioritization of 33 pre-specified needs. Results. Of 215 participants, those aware of their SPMS diagnosis were 57% in Italy vs. 77% in Germany (p=0.004). In both countries, over 80% of aware participants received a SPMS diagnosis from the neurologist; satisfaction with SPMS disclosure was moderate to high. Nevertheless, 28%–35% obtained second opinions, and 48%–56% reported they did not receive any information on SPMS. Participants actively seeking further information were 63% in Germany vs. 31% in Italy (p< 0.001). Variables independently associated to patient awareness were geographic area (odds ratio, OR 0.32, 95% CI 0.13–0.78 for Central Italy; OR 0.21, 95% CI 0.08–0.58 for Southern Italy [vs. Germany]) and activity limitations (OR 7.80, 95% CI 1.47–41.37 for dependent vs. autonomous patients). All pre-specified needs were scored a lot or extremely important, and two prioritized needs were shared by Italian and German patients: ‘physiotherapy’ and ‘active patient care involvement’. The other two differed across countries: ‘an individualized health care plan’ and ‘information on social rights and policies’ in Italy, and ‘psychological support’ and ‘cognitive rehabilitation’ in Germany. Conclusions. Around 40% of SPMS patients were not aware of their disease form indicating a need to improve patient-physician communication. Physiotherapy and active patient care involvement were prioritized in both countries.